Time-Series for the British Post-War Economy - J.C.R. Rowley (Queen's University, Department of Economics, 1969)
One product of the author's recent investigation into the determinants of real fixed capital formation in the post-war british Economy was the following set of time-series. In this paper, the author tells us how the extension of the series beyond the range of the other series resulted in the inclusion of a period during which the rates of the two principal taxes could not be aggregated in a simple linear manner, and the expression for the aggregate tax-rate had to be modified. This break is indicated in the text.
Keywords: 330